2017
DOI: 10.1038/nrrheum.2017.7
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic stem cell transplantation for autoimmune diseases

Abstract: Autologous haematopoietic stem cell transplantation (HSCT) is the only treatment that is able to induce long-term, drug-free and symptom-free remission in several refractory autoimmune rheumatic diseases. Over 3,000 HSCT procedures for rheumatic and nonrheumatic severe autoimmune diseases have been performed worldwide. Specific conditioning regimens are currently used to eradicate the autoreactive immunological memory of patients. Although in vivo immune cell depletion with antithymocyte globulin or anti-CD52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 97 publications
2
112
0
6
Order By: Relevance
“…The differentiation and proliferative potential of these cells theoretically can lead to replacement of diseased tissue in patients and allow scientists to study human disease in vitro with increased precision, potentially tailored to the individual patients from which the cells were derived. 8789 Deriving stem cells from patients offers specific advantages for testing targeted therapeutics and autologous transplantation with reduced risk of rejection. 88 Induced pluripotent stem cells (iPSCs) are stem cells that can be generated from patient tissue by reprogramming processes, and they have greatly enhanced the study of human disease.…”
Section: Crispr-cas Genome Surgery In Human Eye Tissuementioning
confidence: 99%
“…The differentiation and proliferative potential of these cells theoretically can lead to replacement of diseased tissue in patients and allow scientists to study human disease in vitro with increased precision, potentially tailored to the individual patients from which the cells were derived. 8789 Deriving stem cells from patients offers specific advantages for testing targeted therapeutics and autologous transplantation with reduced risk of rejection. 88 Induced pluripotent stem cells (iPSCs) are stem cells that can be generated from patient tissue by reprogramming processes, and they have greatly enhanced the study of human disease.…”
Section: Crispr-cas Genome Surgery In Human Eye Tissuementioning
confidence: 99%
“…45,46 While those are validated, indication for HSCT is defined individually and according to the experience of the center, as this approach is still an experimental therapy. 42,47 Normalization of raised serum interleukin-18 (IL-18) levels has recently been demonstrated posttransplant, hence serum IL-18 may potentially be a useful biomarker to assess disease activity of sJIA in this context. 48,49 Of note, a potential disadvantage of allo-HSCT following a failed autologous procedure is the possibility of adding comorbidities, especially from severe infections (eg, patient 1).…”
Section: Cd25mentioning
confidence: 99%
“…More than 3000 HSCT procedures for severe AIDs have been performed worldwide and the published clinical trials that included sufficient follow-up have demonstrated safety and efficacy of HSCT for AIDs [75,76]. However, the most beneficial effects of stem cell therapies in AIDs are those performed for severe refractory AIDs, particularly systemic sclerosis where a randomized clinical trial has shown significant long-term PFS benefit of HSCT [75][76][77].…”
Section: Journal Of Stem Cell Biology and Transplantation Issn 2575-7725mentioning
confidence: 99%